STRATEGI PENGEMBANGAN DESA WISATA PULESARI SEBAGAI DAYA TARIK WISATA DI SLEMAN, YOGYAKARTA - Syaifulloh, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
Pulesari tourism village is one of the tourism village in Sleman, Yogyakarta. As a tourism village, it has a lot of tourism potential as beautiful river, historic cave, Sebagai salah satu desa wisata, dusun pulesari banyak menyimpan potensi zallaca garden, zallaca dance, kubro siwo dance, pager bumi ceremony and sadranan ceremony. That potential can be fascination for tourist, but it was needed community participation as human resource and government. This is in line with the motto